Transient Thermal Deformation of high performance concrete in the range 20 °C–40 °C. (February 2019) - Cagnon, H.; Vidal, T.; Sellier, A.; Bourbon, X.; Camps, G.
Abstract: Transient Thermal Deformations (TTD) of High Performance Concrete (HPC) having various temperature and compressive loading histories in sealed conditions are investigated experimentally. The aim is to provide accurate data to quantify the transient thermal strain and to specify the conditions required to give rise to the phenomenon. The results are commented and hypotheses proposed to advise practitioners dealing with concrete structures concerned by the conditions of environment and loading that lead to Transient Thermal Deformation.